2002
DOI: 10.4141/a01-018
|View full text |Cite
|
Sign up to set email alerts
|

Performance of steers supplemented with copper before and during receiving at the feedlot

Abstract: . 2002. Performance of steers supplemented with copper before and during receiving at the feedlot. Can. J. Anim. Sci. 82: 87-93. The effects of supplemental Cu in the diets of beef steers grazing winter-annual pasture and(or) during receiving at a feedlot were examined. On 19 February, 84 steers (average BW = 216 ± 1.5 kg) were weighed and randomly assigned to 12 bermudagrass pastures (0.81 ha each) overseeded with wheat, rye, and annual ryegrass (seven steers/pasture). All steers were fed 0.91 kg daily of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…During the last decades, numerous studies have demonstrated the benefits of oral TM supplementation on beef cattle immunity, health and performance [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. However, other studies have shown marginal or insignificant effects of oral TM supplementation on beef cattle metabolism, growth, immunity and health [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. Many of these studies have provided inconsistent results due to differences in mineral forms supplemented (organic versus inorganic), high variability in TM concentration in control diets, the animals’ TM requirements and initial TM status, variation in animal intake and absorption, chemical mineral interactions and antagonisms, level of stress, and differences in experimental models and endpoints.…”
Section: Oral Trace Minerals Supplementation Effects On Beef Cattle H...mentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decades, numerous studies have demonstrated the benefits of oral TM supplementation on beef cattle immunity, health and performance [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. However, other studies have shown marginal or insignificant effects of oral TM supplementation on beef cattle metabolism, growth, immunity and health [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. Many of these studies have provided inconsistent results due to differences in mineral forms supplemented (organic versus inorganic), high variability in TM concentration in control diets, the animals’ TM requirements and initial TM status, variation in animal intake and absorption, chemical mineral interactions and antagonisms, level of stress, and differences in experimental models and endpoints.…”
Section: Oral Trace Minerals Supplementation Effects On Beef Cattle H...mentioning
confidence: 99%
“…Other studies failed to demonstrate positive effects of Cu supplementation on beef cattle health, or had inconsistent results [ 47 , 96 , 97 , 100 , 104 , 115 ]. Stressed calves supplemented with Cu (5 mg/kg DM for 133 d) had increased antibody production (to pig red blood cells) and cell-mediated immune response (to dinitrochlorobenzene stimulation) [ 120 ].…”
Section: Oral Trace Minerals Supplementation Effects On Beef Cattle H...mentioning
confidence: 99%
“…Studies investigating the effect of supplemental Cu in the receiving ration have generally found no benefits on health (Galyean et al, 1995;Beck et al, 2002). However, sheep that are Cu deficient have decreased resistance to bacterial infection (Woolliams et al, 1986).…”
Section: Role Of Trace Mineralsmentioning
confidence: 99%